Antimicrobial Hydroxyethyl-Cellulose-Based Composite Films with Zinc Oxide and Mesoporous Silica Loaded with Cinnamon Essential Oil - Ludmila Motelica; Denisa Ficai; Gabriela Petrisor; Ovidiu-Cristian Oprea; Roxana-Doina Trușcǎ; Anton Ficai; Ecaterina Andronescu; Ariana Hudita; Alina Maria Holban (MDPI AG, 2024)
Background: Cellulose derivatives are gaining much attention in medical research due to their excellent properties such as biocompatibility, hydrophilicity, non-toxicity, sustainability, and low cost. Unfortunately, cellulose does not exhibit antimicrobial activity. However, derivatives like hydroxyethyl cellulose represent a proper matrix to incorporate antimicrobial agents with beneficial therapeutic effects. Methods: Combining more antimicrobial agents into a single composite material can induce stronger antibacterial activity by synergism. Results: Therefore, we have obtained a hydroxyethyl-cellulose-based material loaded with zinc oxide nanoparticles and cinnamon essential oil as the antimicrobial agents. The cinnamon essential oil was loaded in mesoporous silica particles to control its release. Conclusions: The composite films demonstrated high antibacterial activity against Staphylococcus aureus and Escherichia coli strains, impairing the bacterial cells' viability and biofilm development. Such antimicrobial films can be used in various biomedical applications such as topical dressings or as packaging for the food industry.